Additional Notices of Sir Peter Young (Proceedings of the Society of Antiquaries of Scotland, 1863)
Following the preceding article, this paper offers more details about Sir Peter Young’s work as James VI & I’s tutor, as well as the lives of some of his sons. An engraving of Young from 1793 is included in this paper.